Effect of NaOH Solution on Mechanical Properties and Morphology of Fly Ash Based Cold-Pressed Geopolymer - O. Shee-Ween; H. Cheng-Yong; M.M.A.B. Abdullah; O. Wan-En; H. Yong-Jie; T. Hoe-Woon; L. Jia-Ni (Archives of Metallurgy and Materials)
Cold-pressing method is beneficial in reducing the porosity of geopolymer matrix, but the low liquid volume will result in unreacted aluminosilicate materials. This problem can be resolved by increasing sodium hydroxide (NaOH) concentration. This paper thus investigates the effect of NaOH concentration on the properties of cold-pressed geopolymer. The fly ash was activated by sodium silicate (Na2SiO3) and 10, 12, 14 and 16 M of NaOH solution. The dry mix was compacted with a uniaxial hydraulic press and cured for 7 and 28 days. The specimens were measured by porosity and compressive strength measurements. Scanning electron microscopy (SEM) analysis was performed to determine the microstructure of specimens. The geopolymer was optimized at 14 M NaOH with the highest 28-day compressive strength (109.6 MPa) and lowest porosity (8.1%). The SEM micrographs proved that the geopolymer have a dense and compact microstructure.